2021
DOI: 10.1002/pen.25804
|View full text |Cite
|
Sign up to set email alerts
|

Impact of graphene oxide nanoparticles and carbon black on the gamma radiation sensitization of acrylonitrile–butadiene rubber seal materials

Abstract: Seals prepared from acrylonitrile-butadiene rubber (NBR) are primarily used in nuclear services. Nevertheless, at relatively high ionizing radiation doses, NBR seal materials may undergo radiation-induced degradation processes, leading to adverse effects on the sealing ability life. Herein, to strengthen the functional characteristics of NBR seals against radiation, graphene oxide (GO) nanoparticles were prepared and characterized by transmission electron microscopy, X-ray diffraction (XRD), Fourier transform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…3, which includes mycotoxins that are not classified as carcinogenic to humans [ 42 ]. The toxicity of ZEN in vivo was studied by many research mostly reported the hazardous effect of Zearalenone on the reproductive systems either in male or female [ 42 ], also there was a specific concern about the lipid peroxidation of membranes which is included in the means by which ZEN exert its toxic action on human [413, another concern was the findings of [ 44 ] who demonstrated the ability of Zearalenone to disrupt liver functions and affect the liver thoroughly to the degree of suppression of cytochrome P450 in the liver results of our work gave clear data about the distribution of Zearalenone in different body organs which in turn could reveal the most susceptible organs that could suffer from Zearalenone/derivatives toxicity [ [121] , [122] , [123] , [124] , [125] , [126] , [127] , [128] , [129] , [130] , [131] , [132] , [133] , [134] , [135] , [136] , [137] , [138] , [139] , [140] , [141] , [142] , [143] , [144] , [145] ]. By examining the beneficial effect of L. plantarum on the organ exposure to Zearalenone/derivatives, results revealed that although the administration of L. plantarum did not significantly alter the accumulation of [ 125 I]-iodo-ZEN in different mice organs and there were observed similarity in the pattern of Zearalenone distribution through different organs yet there was marked reduction in the Zearalenone concentration in the ovary and that was observed from the 1st 5 min of administration, and since the ovaries are considered the most sensitive (target) organ of Zearalenone toxicity that could provide additional benefit for the use of LAB as it was reported to demonstrate anti-inflammatory, anti-genotoxic and improve ovarian fertility [ 45 ], the decline in the accumulation of [ 125 I]iodo ZEN in mice organs may be attributed to the lactic acid bacterial capability to bind and/or alter ZEN to other compound [ 9 ].…”
Section: Discussionmentioning
confidence: 98%
“…3, which includes mycotoxins that are not classified as carcinogenic to humans [ 42 ]. The toxicity of ZEN in vivo was studied by many research mostly reported the hazardous effect of Zearalenone on the reproductive systems either in male or female [ 42 ], also there was a specific concern about the lipid peroxidation of membranes which is included in the means by which ZEN exert its toxic action on human [413, another concern was the findings of [ 44 ] who demonstrated the ability of Zearalenone to disrupt liver functions and affect the liver thoroughly to the degree of suppression of cytochrome P450 in the liver results of our work gave clear data about the distribution of Zearalenone in different body organs which in turn could reveal the most susceptible organs that could suffer from Zearalenone/derivatives toxicity [ [121] , [122] , [123] , [124] , [125] , [126] , [127] , [128] , [129] , [130] , [131] , [132] , [133] , [134] , [135] , [136] , [137] , [138] , [139] , [140] , [141] , [142] , [143] , [144] , [145] ]. By examining the beneficial effect of L. plantarum on the organ exposure to Zearalenone/derivatives, results revealed that although the administration of L. plantarum did not significantly alter the accumulation of [ 125 I]-iodo-ZEN in different mice organs and there were observed similarity in the pattern of Zearalenone distribution through different organs yet there was marked reduction in the Zearalenone concentration in the ovary and that was observed from the 1st 5 min of administration, and since the ovaries are considered the most sensitive (target) organ of Zearalenone toxicity that could provide additional benefit for the use of LAB as it was reported to demonstrate anti-inflammatory, anti-genotoxic and improve ovarian fertility [ 45 ], the decline in the accumulation of [ 125 I]iodo ZEN in mice organs may be attributed to the lactic acid bacterial capability to bind and/or alter ZEN to other compound [ 9 ].…”
Section: Discussionmentioning
confidence: 98%
“…It is interesting to mention that graphene can be modified by other kinds of methods such as gamma irradiation, 96–99 electrochemical methods, 44,100,101 and heat treatment. 61,102–104…”
Section: Graphenementioning
confidence: 99%
“…which is higher than the two radiotracers [ 131 I] iodosulfasalazine and [ 131 I] iodobalsalazide gave 75.5 and 73 % at 24 hours postinjection. according to [111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126]. Therefore, it is clear that (PPAR) antagonist expression levels rise at the onset of the disease, and the radiotracer is anticipated to interact with that receptor, which is strongly expressed in the target organ, ulcerative colitis.…”
Section: -Investigations Using Molecular Modellingmentioning
confidence: 99%